A Narrative Study; Speaking Exposure Undergone by Members of ESA (English Student Association) at University of Islam Malang) - Muhammad Khoirun Najib (Graduate Program, University of Islam Malang, 2021)
The aim of this study is to analyze and investigate how the speaking exposure undergone by members of ESA. Then, the result of study can give relevant information for improving English speaking skill. These are the reasons as stated above why the present study was designed. How the speaking exposure undergone by members of ESA was investigated through narrative study with semi-structured interview. Three selected members of ESA (respondents) were involved in this research. They all are from members of English Student Association at University of Islam Malang. This study employed qualitative data analyses. The qualitative data were gained from the transcribed interviews (spoken discourse). The findings of the study yielded that in terms of speaking exposure received by members of ESA, the respondents were found to be easy in gaining speaking exposure in most of the English programs in ESA. They are easy to obtain the speaking exposure because the respondents are very active in joining and participating English activities. Further, based on the data gathered from most of respondents’ voice about speaking exposure, it is clear that speaking skill needs to have more chances to enhance the English speaking. Keywords: narrative study, speaking exposure, English Student Association.